Hubungan Pengetahuan Ibu dengan Pemberian Kolostrum pada Bayi Baru Lahir di PMB Fitri Kota Bengkulu Tahun 2025 - Julianike Irmanda; Liya Lugita Sari; Febra Ayudiah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Colostrum is breast milk produced from the first day to the third day after childbirth. It is thick, yellowish in color, and represents the first fluid secreted by the mammary glands during this period. Colostrum contains essential nutrients and antibodies that play a vital role in strengthening the immune system and supporting the health of newborns. Objective: This study aimed to determine the relationship between maternal knowledge and colostrum feeding among newborns at PMB Fitri, Bengkulu City, in 2025.Methods: This research employed an analytical observational quantitative design with a cross-sectional approach. The sample consisted of 31 mothers selected through purposive sampling. Data were collected using a questionnaire, and analysis was performed using the Chi-Square test. Results: Most respondents had a moderate level of knowledge (38.7%), and the majority had provided colostrum to their babies (64.5%). However, statistical analysis revealed no significant relationship between maternal knowledge and colostrum feeding (p-value = 0.126 > 0.05). Conclusion: There was no statistically significant relationship between maternal knowledge and colostrum feeding among newborns at PMB Fitri, Bengkulu City, in 2025.